2021
DOI: 10.3233/jad-210491
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Periodontitis and Alzheimer’s Disease: How to Hit Two Birds with One Stone

Abstract: Alzheimer’s disease (AD) is the leading cause of cognitive impairment in the elderly. Recent evidence suggests that preventive interventional trials could significantly reduce the risk for development of dementia. Periodontitis is the most common dental disease characterized by chronic inflammation and loss of alveolar bone and perialveolar attachment of teeth. Growing number of studies propose a potential link between periodontitis and neurodegeneration. In the first part of the paper, we overview case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 125 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…Statistically significant differences in TNF-α and IL-1 expressions were observed in treated organs compared to control organs. This result was similar to previous reports that an overreaction in host response can occur that results in IL-1 and TNF-α and leading to the loss of periodontal attachment (Werber et al, 2021). MIF could induce IL-1 and TNF-α (Howait et al, 2019;Jiao et al, 2020).…”
Section: Mif Tnf-α and Il-1tissue Levelssupporting
confidence: 92%
“…Statistically significant differences in TNF-α and IL-1 expressions were observed in treated organs compared to control organs. This result was similar to previous reports that an overreaction in host response can occur that results in IL-1 and TNF-α and leading to the loss of periodontal attachment (Werber et al, 2021). MIF could induce IL-1 and TNF-α (Howait et al, 2019;Jiao et al, 2020).…”
Section: Mif Tnf-α and Il-1tissue Levelssupporting
confidence: 92%
“…The results showed that tooth loss, the depth of periodontal pockets, and the degree of alveolar bone loss are related to cognitive impairment, especially when they are older than 45 years old. 153 A prospective follow-up survey of 5468 subjects found that irregular tooth brushing habits are also related to Alzheimer’s disease. 154 A survey in the United States found that there is an association between periodontitis and cognitive impairment in 2355 60-years and older people.…”
Section: Oral Microbes and Alzheimer’s Diseasementioning
confidence: 99%
“…Alzheimer's disease remains an incurable disease that affects 47 million people worldwide. This disease has also been linked to periodontal disease, and the severity of periodontal disease, small number of remaining teeth, and irregular tooth brushing habits are risk factors for Alzheimer's disease; preventive effects are expected by improving these factors (112)(113)(114). IgA nephropathy is one of the main causes of chronic kidney disease.…”
Section: Association Between Oral Microbiota and Systemic Diseasesmentioning
confidence: 99%